2015
DOI: 10.4236/oalib.1102066
|View full text |Cite
|
Sign up to set email alerts
|

Neglected Dislocation of the Elbow: About 8 Cases and Review of Literature

Abstract: The authors report eight cases of neglected dislocations of the elbow. The fracture-dislocations were included in our series. All patients benefited from a surgical reduction. In five cases, an internal fixation by K-wires was necessary. All patients benefited from physical therapy after removal of osteosynthesis material. After a mean follow-up of 20 months, we noted 50% of satisfactory functional results according to Mayo Elbow Performance Score. Neglected dislocations of elbow remain a rather frequent entit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“… 7 , 19 This study reported that three patients were excellent and six patients were good in this series of nine patients. This result is similar to other series conducted by Anderson et al 8 (mean MEPI of 93 and good or excellent outcomes in 97% of patients), Mehta et al 20 (mean MEPI of 89 with 80% of patients having excellent and good results), and Coulibaly et al 12 (mean MEPI of 86 with 82% of patients having excellent and good results).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“… 7 , 19 This study reported that three patients were excellent and six patients were good in this series of nine patients. This result is similar to other series conducted by Anderson et al 8 (mean MEPI of 93 and good or excellent outcomes in 97% of patients), Mehta et al 20 (mean MEPI of 89 with 80% of patients having excellent and good results), and Coulibaly et al 12 (mean MEPI of 86 with 82% of patients having excellent and good results).…”
Section: Discussionsupporting
confidence: 91%
“…1,2,6 How does the patient tolerate the associated elbow stiffness and the onset of dislocation as basic indications for surgery? 2,6,[8][9][10][11] Martini et al proposed that elbow flexion of 80°-90° correlates with functional stiffness. In such cases, surgery should not be performed.…”
Section: Discussionmentioning
confidence: 99%